Study on the Concept of Sketching and Aesthetic Value Reflected in Xin Dongwang’s Oil Paintings - Gao, Xiaopeng (Journal of Roi Kaensarn Academi, 2024)
This study aims to examine the sketching concept and aesthetic value in contemporary Chinese oil painter Xin Dongwang’s artistic creation, with a particular focus on how sketching techniques serve as a unique medium for emotional and philosophical expression. The research employs a qualitative methodology combining artistic analysis and theoretical research through case studies and literature review. The study analyzes two representative works by Xin Dongwang: "Mountains and Rivers" and "Growth", using visual analysis techniques and theoretical framework examination. Research tools include artwork documentation analysis, historical context review, and comparative analysis of traditional and contemporary sketching techniques. Data analysis involves systematic examination of artistic elements, technical approaches, and philosophical implications in Xin Dongwang’s works, supported by relevant literature on Chinese oil painting development and sketching traditions. The findings reveal that Xin Dongwang’s sketching techniques uniquely bridge traditional Chinese aesthetics and modern oil painting methods. The research demonstrates that his sketching approach: (1) integrates traditional techniques with contemporary expression, (2) achieves profound emotional depth through direct observation of nature and life, and (3) establishes a distinctive oil painting style with Chinese cultural characteristics. These findings contribute to both the theoretical understanding of contemporary Chinese oil painting and the practical development of sketching techniques in modern artistic creation.